2007
DOI: 10.1007/s00068-007-6134-5
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hemiarthroplasty for Proximal Humeral Fractures in the Elderly: Long-Term Functional Outcome and Social Implications

Abstract: Background: Primary shoulder hemiarthroplasty is an established treatment modality for complex fractures of the proximal humerus. Long-term functional outcome is often disappointing. However, little is known about social implications particularly in the elderly. Methods: A single-institution case series of consecutive geriatric patients (age > 70 years) treated with shoulder hemiarthroplasty for complex fractures of the proximal humerus between 1994 and 1997 was analysed. Postoperative morbidity, long-term fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A study on the social implications of SHA for proximal humeral fractures in patients older than 70 years found that 85% of patients lived in their own environment and managed daily life despite poor shoulder function (Dietrich et al. 2007). Furthermore, the difference in functional outcome between younger and elderly patients might be due to differences in general health condition and in the mechanisms of trauma.…”
Section: Discussionmentioning
confidence: 99%
“…A study on the social implications of SHA for proximal humeral fractures in patients older than 70 years found that 85% of patients lived in their own environment and managed daily life despite poor shoulder function (Dietrich et al. 2007). Furthermore, the difference in functional outcome between younger and elderly patients might be due to differences in general health condition and in the mechanisms of trauma.…”
Section: Discussionmentioning
confidence: 99%
“…A similar discrepancy was found in another study reporting functional outcome scores and social implications of hemiarthroplasty treatment of proximal humeral fractures in the elderly. 11 The patients had a median age of 80 years and suffered from mainly 3- and 4-part fractures. The authors found that 41 out of 48 elderly patients managed their daily lives and lived in their own homes for four years after their hemiarthroplasty, despite a mean CMS of 41.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of stemmed hemiarthroplasty for acute fractures are, however, unpredictable and often disappointing. 1 , 7 , 11 , 17 , 22 , 25 Randomized clinical trials have reported similar poor functional outcome of hemiarthroplasty and nonoperative treatment for displaced 4-part fractures. 6 , 23 …”
mentioning
confidence: 97%